2020
DOI: 10.1016/j.ejmg.2020.103972
|View full text |Cite
|
Sign up to set email alerts
|

Focal segmental glomerulosclerosis and mild intellectual disability in a patient with a novel de novo truncating TRIM8 mutation

Abstract: Mutations in the TRIM8 gene have been described in patients with severe developmental delay, intellectual disability and epilepsy. Only six patients have been described to date. All the previous mutations were truncating variants clustered in the C-terminus of the protein. A previous patient with TRIM8-related epileptic encephalopathy was reported to have nephrotic syndrome. Here we describe the clinical, radiological and histological features of an 8-yearold male patient with a TRIM8 mutation who, in contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…[44][45][46] TRIM8 disease-associated variants are restricted to the last exon (Figures 1C and S2). 23,[41][42][43] Combining our findings with previous reports showed that four individuals from distinct ethnic backgrounds share the identical variant at position c.1375 and two share nonsense variants at position c.1380 (Figure S2). 23,41 This observation suggests that this region is a recurrent germline variant hotspot (Figure S2, Table 1), as has been demonstrated for other rare dominant monogenic causes of syndromic epilepsy 47 and nephrotic syndrome.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…[44][45][46] TRIM8 disease-associated variants are restricted to the last exon (Figures 1C and S2). 23,[41][42][43] Combining our findings with previous reports showed that four individuals from distinct ethnic backgrounds share the identical variant at position c.1375 and two share nonsense variants at position c.1380 (Figure S2). 23,41 This observation suggests that this region is a recurrent germline variant hotspot (Figure S2, Table 1), as has been demonstrated for other rare dominant monogenic causes of syndromic epilepsy 47 and nephrotic syndrome.…”
supporting
confidence: 87%
“…All subjects were diagnosed with renal disease after (10/12) or at the time of (2/12) the development of neurologic disease. Previous case reports have described truncating DNVs in TRIM8 in a total of eight children with developmental delay and epilepsy, but only three of these subjects were described to have nephrotic syndrome (Figure S2), 23,[41][42][43] which left it unsolved whether the renal disease was associated to TRIM8 variants or just coincidental. The early ascertainment of these cases is also consistent with our observation that renal disease presents later in the course of these patients and may not have been apparent yet at the time of these reports.…”
mentioning
confidence: 98%
“…To date, at least eight reported individuals have been associated with heterozygous truncating variants in TRIM8 , all of whom developed epilepsy or epileptic encephalopathy, including five individuals with proteinuria (Table 1 and Fig. 4 ) [ 3 6 ]. The present patient did not present with any neurological manifestations such as developmental delay and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…4 , patient IX). Nevertheless, the variant of patient III, who had mild developmental delay and well-controlled epilepsy [ 6 ], was located more 5’ in the last exon than 5 patients with epileptic encephalopathy reported by Assoum et al and Warren et al [ 4 , 5 ]. Therefore, a difference in the size of the truncated protein may not explain the difference in the severity of the neurological phenotype [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation